A Brief Review on Impact of Social Network Mining on Online Shopping for Classifying Customers - SK, Mishra; Agarwal, A (International Journal of Computer Sciences and Engineering, 2019)
Communication is the only way to exchange views and feelings. If communication between two parties is strong, there must always be more trust and decisions are taken firmly. Social networking sites are the potential tools which are utilized for communication without much physical efforts. Nowadays, the Social Networking phenomenon is spread over the globe and affects every individual who uses a social medium to communicate with others. Social networking sites have revolutionized the way companies communicate with their customers. The reachability of companies to customers has drastically improved because of the revolution in mobile technology. The main goal of our work is to get the insight into the impact of social networking on customer behavior, to explain why, when, and how social media has impacted on the customer decision process. We briefly introduce various laws used in mining techniques and the concept of link analyzis used for analyzing the data gathered from social networking sites. We explain the concept of centrality in social networks and exponential growth in online shopping and the causes behind this trend are also analyzed as well.